Burkholderia vietnamiensis Causing Bacteremia in Patients Suffering from B-Cell Acute Lymphocytic Leukemia: A Case Series and Review of Literature - Kar, Mitra; Dubey, Akanksha; Sahu, Chinmoy; Patel, Sangram Singh (Journal of Laboratory Physicians, 2023)
Burkholderia cepacia complex consists of 24 species of microorganisms that include B. cepacia, B. multivorans, B. cenocepacia, B. vietnamiensis, B. ambifaria, and many more. It is a ubiquitous microorganism found in the soil and aquatic milieu. The probability of infections in immunocompetent individuals is rare, but an increase in the population of immunocompromised patients in the past decade has attributed to increasing incidence of infections caused by these microorganisms. The most common infections caused by these isolates include bacteremia, pneumonia, genital tract infections, and surgical wound infections. Their potential to cause nosocomial outbreaks in wards of immunocompromised patients is well known. In this case series, we describe three cases of community-acquired Burkholderia vietnamiensis bacteremia in patients suffering from B-cell acute lymphocytic leukemia and their antibiotic sensitivity pattern to guide the treatment of these individuals.
Keywords: Burkholderia cepacia complex (BCC); hematological malignancies; immunocompromised individuals; bacteremia; Burkholderia vietnamiensis